Factors that affect consumption on debit card / Amsyar Azizi and Azimah Adnan - Azizi, Amsyar; Adnan, Azimah (Faculty of Business and Management, 2013)
The purpose of this study is to determine the factor that affects consumption on debit card. Only 300 of respondents which are staff in PETRONAS and PETROFAC were selected and act as respondents for this study. The objectives of this study aims to identify the factors that contributes to the consumption on debit card and to ascertain the best predictor to influence consumption on debit card. This study also takes into consideration of the respondents’ payment behavior, safety, customer attitude and acceptance. Besides that, this study is a quantitative research study whereby the findings of the study were analysed by using the Statistical Package for the Social Sciences (SPSS). Next, the data collected in this study is analysed by using frequency, descriptive analysis, reliability, Pearson’s correlation analysis and multiple regressions in order to achieved the research objectives. Eventually, this study discovered that most of the respondents were female, age around 25 to 34, married, degree holder, and most of them have monthly salary range between RM1001 to RM3000. In addition, multiple regressions also answered the research objective one whereby payment behavior, safety, customer attitude and acceptance becomes the factors that contributed towards consumption on debit card since p-value is less than 0.05. In order to answer the research objective two, payment behavior which has the highest t-value is became the best factors to influence the consumption on debit card. There is also recommendation in this study which to emphasize the personal finance course to school and consumer should aware on what they are spending when using debit card.